TOR acts as a metabolic gatekeeper for auxin-dependent lateral root initiation in Arabidopsis thaliana - Stitz, Michael; Kuster, David; Reinert, Maximilian; Schepetilnikov, Mikhail; Berthet, Béatrice; Reyes Hernández, Blanca Jazmín; Janocha, Denis; Artins, Anthony; Boix, Marc; Henriques, Rossana; Pfeiffer, Anne; Lohmann, Jan U.; et al. (The EMBO journal, 2023)
Abstract Plant organogenesis requires matching the available metabolic resources to developmental programs. In Arabidopsis, the root system is determined by primary root-derived lateral roots (LRs), and adventitious roots (ARs) formed from non-root organs. Lateral root formation entails the auxin-dependent activation of transcription factors ARF7, ARF19, and LBD16. Adventitious root formation relies on LBD16 activation by auxin and WOX11. The allocation of shoot-derived sugar to the roots influences branching, but how its availability is sensed for LRs formation remains unknown. We combine metabolic profiling with cell-specific interference to show that LRs switch to glycolysis and consume carbohydrates. The target-of-rapamycin (TOR) kinase is activated in the lateral root domain. Interfering with TOR kinase blocks LR initiation while promoting AR formation. The target-of-rapamycin inhibition marginally affects the auxin-induced transcriptional response of the pericycle but attenuates the translation of ARF19, ARF7, and LBD16. TOR inhibition induces WOX11 transcription in these cells, yet no root branching occurs as TOR controls LBD16 translation. TOR is a central gatekeeper for root branching that integrates local auxin-dependent pathways with systemic metabolic signals, modulating the translation of auxin-induced genes.